Pengaturan Hak Kekayaan Intelektual dalam Masyarakat Ekonomi Asean dan Implikasinya bagi Indonesia - Magdariza, Magdariza (Universitas Ekasakti, 2023)
Nowadays, the intellectual property rights (IPR) have received great attention from countries related to the utilization of IPR that can be of high economic value. In the blueprint of the ASEAN Economic Community 2015 also contains that ASEAN wants to realize a single market with free traffic flow, among other things, to the field of Intellectual Property Rights (IPR). The problems in this research are firstly, how is the system of intellectual property rights (IPR) protection in the framework of trade liberalization in ASEAN Economic Community ?; and secondly, what are the implications of the application of the intellectual property rights system within the framework of ASEAN to the regulation of intellectual property rights (IPR) in Indonesia?. This research is a legal research that is juridical normative with legal history and legal comparison approaches, emphasizing on secondary data obtained from literature study and supported by primary data in the form of interviews obtained from field research. The specification of this research is descriptive analytical. The data collected were analyzed by qualitative juridical. The results of this study are; Firstly, the legal protection system of Intellectual Property Rights in ASEAN in the framework of trade liberalization through the ASEAN Economic Community 2015 is based on the ASEAN Intellectual Property Rights Action Plan 2011-2015/ASEAN IPR and ASEAN Charter. Furthermore, the two legal instruments are within the content of ASEAN Intellectual Property Rights Action Plan 2011-2015 and the Preamble of ASEAN Charter and Article 1 (points 5, 6 and 11). The ASEAN Charter contains the concept of Welfare State law in which the purpose of the provisions of such law shall be one of them in the framework of the interests of the welfare of ASEAN society as existing in the concept of the welfare state; and Secondly, in the framework of the realization of the ASEAN IPR Action Plan 2011-2015 in the ASEAN Economic Community, then Indonesia has adjusted by amending several regulations of legislation which are within the scope of intellectual property rights such as the Law no. 19 of 2002 with the Law no. 28 of 2014 on Copyright and the Law no. 15 of 2001 with Law no. 20 of 2016 on Trademarks and Geographical Indications to deal with the era of global trade.